BRINE SHRIMP TEST TRITERPENES FROM ROOT BARK OF Sandoricum emarginatum - Pratiwi Pudjiastuti; Suyanto; Sudestry Manik; Cicik S. Cahyandari; Alfinda N. Kristanti (The East Java Biological Society, 1997)
The root of Sondoricum emargiatum, Meliaceae was collected in North Tapanuli, North Sumatera. Local people use this timber plant for construction and the fruit bark for cooking (Naito, 1986). In the previous investigation, 1,3,4 cuparatrien-15-ol, 4.15-cubebene and secobryononic acid were isolated from stem bark of Sondoricum emargiatum (Pratiwi). Further fractionation of n-hexane extract of root bark of Sondoricum emargiatum in the isolation of two triterpenes resulted byononic (1) and 3,4-seco-olean-4 (23), 12-dien-3,29-dionic acids (3) and their structures were elucidated by IR, MS, and NMR-spectroscopy. Compound (1) and (3) were forund more active than methyl bryononic derivate (2) with Brine Shrimp as bioindicator.